Inflammation, Cognition, and White Matter in Older Adults: An Examination by Race - Boots, Elizabeth A.; Castellanos, Karla J.; Zhan, Liang; Barnes, Lisa L.; Tussing-Humphreys, Lisa; Deoni, Sean C. L.; Lamar, Melissa (Frontiers in Aging Neuroscience, 2020)
Objectives: Non-Latino Blacks have greater risk for Alzheimer’s dementia compared to non-Latino Whites, possibly due to factors disproportionally affecting Blacks including cardiovascular disease (CVD). Chronic peripheral inflammation is implicated in both Alzheimer’s dementia and CVD and is known to impact cognition and cerebral white matter, yet little work has examined these associations by race. This study examined associations between inflammation, cognition, and cerebral white matter generally, and by race.Methods: Eighty-six non-demented older Black and White participants (age=69.03; 50% female; 45% Black) underwent fasting venipuncture, cognitive testing, and MRI. Serum was assayed for interleukin-6 (IL-6), C-reactive protein (CRP), and interleukin 1-beta. Cognitive domains included memory, executive function, and attention/information processing. MRI measures included white matter hyperintensity volumes (WMH) and quantification of white matter integrity in areas outside WMHs via DTI-derived fractional anisotropy (FA) and mean diffusivity, as well as multi-component relaxometry derived myelin water fraction (MWF). Results: Blacks and Whites did not differ on age, sex, or CVD risk; Blacks had lower word reading scores. Separate linear regression models adjusting for relevant confounders revealed that higher IL-6 associated with lower executive function and higher CRP levels associated with lower FA and MWF. Stratified analyses revealed that these association were significant for Blacks only. Discussion: These findings suggest that peripheral inflammation is inversely associated with select cognitive domains and white matter integrity (but not WMHs), particularly in Blacks. It is important to consider race when investigating inflammatory associates of brain and behavior.